Taxonomy of the Oriental leafhopper genus Favintiga Webb (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) with description of a new species from China - Lu, Lin; Zhang, Yalin (Zootaxa, 2018)
The Oriental leafhopper genus Favintiga Webb is reviewed. A checklist to the species is provided together with a key for their separation. The genus contains three species: F. camphorae (Matsumura), F. gracilipenis Shang & Zhang and F. paragracilipenis sp. nov., the latter described here from the Jianfengling Mountains, Hainan, China.